Fresno County Bar Association's Barristers Benefit Ball at the Fresno Metropolitan Museum - Watkins, Howard::::::::: (1988)
Michael Jens Frederick Smith, Jana Smith, Nina Scribner, Robert Scribner, Steven McClean, Denise McClean, Denise Routhier, and David Gilmore